THE INFLUENCE OF FINANCIAL LITERACY AND DIGITAL FINANCIAL RECORDING ON THE FINANCIAL RESILIENCE OF MSMES WITH INTELLECTUAL CAPITAL AS A MEDIATING VARIABLE - Hadiah Fitriyah; Natasya Shobibatur Rokhmah (International Journal of Economic Integration and Regional Competitiveness, 2026)
Abstract. This study aims to analyze the effect of financial literacy and digital financial record-keeping on the financial resilience of culinary MSMEs in Sidoarjo, with intellectual capital as a mediating variable. This research is motivated by the importance of MSMEs’ ability to maintain business financial stability amid changing economic conditions and the development of digital technology. The research method used is a quantitative approach with data collection techniques through questionnaires distributed to 30 culinary MSME owners in Sidoarjo. Data analysis was conducted using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method with the assistance of SmartPLS software. The results show that financial literacy and digital financial record-keeping do not have a direct significant effect on the financial resilience of MSMEs. However, both variables have a positive and significant effect on intellectual capital, and intellectual capital significantly affects the financial resilience of MSMEs. In addition, intellectual capital is proven to fully mediate the effect of financial literacy and digital financial record-keeping on the financial resilience of MSMEs. Therefore, the financial resilience of MSMEs is more influenced by the ability of business actors to manage knowledge, work systems, and intellectual resources.